Effect of Consumer Perceptions About Services PT Pos Indonesia and Brand Lift against the interest Reuse Postal Service Express (Pos Indonesia) - Wicaksono, Randy Ardianto; S.Sos, MM, Djoko Setyabudi (Interaksi Online, 2016)
PT Pos Indonesia is a state-owned enterprise or government moves to serve customers in the field of logistics service or shipping services. The presence of other logistics services such as and others either privately owned or foreign make increasingly tight competition among logistics services. The amount of the logistics industry in this Indoneisa make businesses try to improve and quality service to make the company become top of mind in people's minds and have a positive image to the public. The rationale used is Stimulusm Organism response theory and Expectancy Value Theory with supporting theory Resoned Action Theory. This research type is explanatory research. This study used a technique Non-Probability Sampling with accidental sampling method in determining sampling. Total sample of 100 who have met the criteria already used the services of logistics PT Pos Indonesia aged 20-65 years in the city of Semarang.The first hypothesis test results showed that the variables of consumer perceptions about the services of PT Pos Indonesia (X1) affect the interest of using the return services of Pos Express (Y) and showed significant results with the results of 0,000 or probability <0,5 and the contribution of the effect as much as 71.2%. Test the hypothesis of the second image shows variable meerek (X2) befrpengaruh positive and significant interest in reusing the services of the Post Express (Pos Indonesia) (Y) with significant value 0,000 or probability < 0.5 and the contribution of the effect as much as 74.0% this mark contribution is high. Advice can be given is Pos Indonesia to continue to use a variety of strategies unutuk improve its quality is not inferior to that of its competitors who are also opening branch offices in various regions